Use of forensic databases by Police X Archives - Moszczyński, Jarosław (Acta Universitatis Lodziensis. Folia Iuridica, 2018)
Police Teams Dealing with Undetected Crime, commonly referred to as the X Archives, operate within the voivodship police headquarters. They accumulate the most experienced officers and deal with the most serious crimes from the past, mainly the murders whose perpetrators have not been detected so far. The teams of several people make a thorough analysis of the acts of undetected crimes, they reach sources of information and use the latest achievements of forensic science. Two databases are particularly useful, i.e. AFIS and DNA. For this reason, the most attention has been given to them.